PERANCANGAN APLIKASI PENERJEMAH OTOMATIS BAHASA SUNGAILIAT KABUPATEN BANGKA KE BAHASA INDONESIA - Ahmat Josi (Jurnal Mantik Penusa, 2019)
Language translator is the process of finding equivalent source language texts (BSU) to be placed as target language texts, in principle language translators aim to help find out the meaning of a particular language. Indonesia has a wide variety of regional languages, one of which is the Sungailiat language of Bangka Regency. sungailiat language is one of the Malay language family. In general, its function is as a means of communication or connecting in daily conversation. In addition, other functions as a sign or an identity or a symbol of pride in the Bangka Belitung Islands Province. in this study the researcher will design / blueprint an android application that functions to translate the sungailiat language into Indonesian automatically using the voice or text feature.Keywords: translator, design, application, real estate, language